Mapping the entertainment ecosystem of Wattpad: Platforms, publishing and adaptation. (April 2021) - Parnell, Claire
Digital platforms have reshaped the creative industries and restructured relationships between media sectors. Creative writing and reading social media platforms like Wattpad are challenging what it means to publish fiction in the early 21st century, and digital streaming platforms like Netflix, Hulu and others have begun looking to these platforms to source creative content for adaptation. Praxis on creative writing social media platforms is shaped by a complex and ongoing interplay between the technocultural and socio-economic conditions of platforms and their users. This article argues for an integration of publishing studies and platform studies by applying a media ecology framework to map behaviour on Wattpad, one of the largest creative writing social media platforms, and the relationships it has developed with other media companies. Specifically, it draws on and extends José van Dijck's ((2013) The Culture of Connectivity: A Critical History of Social Media . New York, NY: Oxford University Press.) microsystem/ecosystem connective media model and proposes a broader conceptualisation of the entertainment ecosystem that incorporates adaptation of content across the book publishing and entertainment media sectors. Mapping these platforms alongside legacy media and publishing companies offers a productive framework for theorising contemporary entertainment media production within the platform media landscape.